NURSING PERFORMANCE IN PREVENTING HOSPITAL INFECTIONS IN INTENSIVE CARE UNITS: A LITERATURE REVIEW (REMUNOM, 2025)
Healthcare-associated infections (HAIs) represent a serious public health problem, especially in high-complexity hospital settings such as Intensive Care Units (ICUs). These infections, which can be caused by various pathogens, lead to increased mortality, with higher prevalence in ICUs due to patients' immunological fragility and the high number of invasive procedures, prolonged hospitalizations, and elevated hospital costs, highlighting the need for effective preventive measures. The nursing staff plays a crucial role in preventing HAIs, emphasizing the importance of practices such as proper hand hygiene, maintaining aseptic procedures, and correct use of invasive devices. A literature review has shown that the implementation of national programs and the efforts of Hospital Infection Control Committees (CCIH) have contributed to the reduction of HAIs. However, challenges persist, especially in middle- and low-income countries where infection rates remain high. Continuous training of the multidisciplinary team and strict adherence to preventive measures are essential to minimize risks and improve patients' clinical outcomes. This descriptive work is based on a literature review of articles published in the last five years, aiming to identify nursing actions in the prevention of HAIs in ICUs. It concludes that the adoption of standardized preventive measures and staff awareness are essential to reduce the incidence of these infections, contributing to patient safety and the efficiency of healthcare systems.